STRATEGI KEUNGGULAN BERSAING PADA KACANG GARING MARTABE DALAM MENGHADAPI PERSAINGAN ANTAR KACANG GARING DI SILANGKITANG – TAPANULI UTARA - Marta Lestari Nababan (Jurnal Niaga & Bisnis (e-journal), 2015)
This study aims to assess the strengths and weaknesses (internal) and the opportunities and threats (external) owned by Kacang Garing Martabe, used by author to determine the exact strategy to be applied by Kacang Garing Martabe to face the competition between Kacang Garing in North Tapanuli. From the analysis using the EFE Matrix, Kacang Garing Martabe has  value  2.3 which indicates that the reaction of company to the company’s internal factors belong to average. While the internal condition assessed using IFE matrix showed that Kacang Garing Martabe has value 2.9 which indicates that internal’s position of Kacang Garing Martabe belong to strong. The results of the CPM, the indicator’s value of competition are as follows: Kacang Garing Martabe (3.3), Kacang Garing Sihobuk Exon (3.05) and Kacang Garing Sihobuk Ancim (2.65). There are 8 key factors that influence the competition on Kacang Garing Martabe: Price competitiveness, quality of product, innovation of product, business experience, location, operational cost, organizational structure and quality of service. The next stage is matching stage. This stage is performed by using two analytical tools, SWOT Matrix and IE Matrix. From the results of SWOT analysis are found that Kacang Garing Martabe is in quadrant I, it means that the companies are located in the first quadrant is a company that supports the aggressive strategy. And according to IE Matrix, position of Kacang Garing Martabe is in quadrant V (five) called keep and maintain strategy. The last stage is decision stage. By using QSPM the two alternative strategies are given weights and ratings based on a strategic key factors in the company. From a qualitative analysis using QSPM found that market penetration strategy has a total value of 6.65 while the appeal of the product development strategy has a total value of appeal at 6,25. Competitive strategy recommended to Kacang Garing Martabe is market penetration strategy.